2008
DOI: 10.1097/fpc.0b013e3283117d67
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug resistance in epilepsy and polymorphisms in the voltage-gated sodium channel genes SCN1A, SCN2A, and SCN3A: correlation among phenotype, genotype, and mRNA expression

Abstract: Results of this study suggest an association between SCN2A IVS7-32A>G and AED responsiveness, without evidence of an effect on splicing or mRNA expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(64 citation statements)
references
References 24 publications
1
61
0
2
Order By: Relevance
“…[11][12][13] Studies examining SCN1A genotype and clinical response have likewise focused primarily on the rs3812718 polymorphism with some examining the non-synonymous single-nucleotide polymorphism (SNP), rs2298771 (3199A4G), and have failed to demonstrate any associations. 11,[14][15][16][17][18][19][20] To date, only Kwan and colleagues 20 have used a haplotype tagging methodology to fully examine SCN1A variations and clinical response to sodium channel blocking drugs. They found no SCN1A associations in their group of Chinese epilepsy patients.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] Studies examining SCN1A genotype and clinical response have likewise focused primarily on the rs3812718 polymorphism with some examining the non-synonymous single-nucleotide polymorphism (SNP), rs2298771 (3199A4G), and have failed to demonstrate any associations. 11,[14][15][16][17][18][19][20] To date, only Kwan and colleagues 20 have used a haplotype tagging methodology to fully examine SCN1A variations and clinical response to sodium channel blocking drugs. They found no SCN1A associations in their group of Chinese epilepsy patients.…”
Section: Introductionmentioning
confidence: 99%
“…Use-dependent blockade of the fast Na current in dentate granule cells by carbamazepine is lost in hippocampi resected from patients with carbamazepine-resistant temporal-lobe epilepsy, although this fi nding does not extend to lamotrigine, which has a pharmacologic action similar to that of carbamazepine. Polymorphisms of the SCN2A gene, which encodes the α2 subunit of the neuronal Na channels, were found to be associated with resistance to AEDs in general as well as to those that act on the sodium channels (Kwan et al 2008 ). Whether these changes result in reduced sensitivity to antiepileptic drugs that act on the receptor is unknown.…”
Section: Drug Resistance In Epilepsymentioning
confidence: 98%
“…However, another study conducted in Japanese revealed a positive association between the genetic variation of IVS5-19 G>A and CBZ resistance [13]. In addition, a study has reported a positive association between SNP of SCN2A IVS7-32 G>A and AED resistance in Hong Kong Chinese [14]. Nevertheless, there is as yet no definite evidence suggesting the association between the genetic variation of SCN1A and the different responses to AED Other AED targets, where functional polymorphisms could possibly influence the clinical treatment response, are GABA A receptors.…”
Section: Genetic Variations In Individuals That May Affect Pharmacodymentioning
confidence: 99%